2017
DOI: 10.3390/ma10091044
|View full text |Cite
|
Sign up to set email alerts
|

Composite Fibers from Recycled Plastics Using Melt Centrifugal Spinning

Abstract: New methods are being developed to enable the production of value-added materials from high-volume, low-cost feedstocks arising from domestic recycling streams. In this work, recycled bottle-grade polyethylene terephthalate, polystyrene, and polypropylene were spun into fibers from the melt using a centrifugal spinning technique. Mono-component fibers and 50/50 blends of each polymer and a 33/33/33 blend of all three polymers were evaluated. Fiber morphology, chemistry, thermal, and mechanical properties were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 32 publications
(43 reference statements)
0
12
0
2
Order By: Relevance
“…Although there are many advantages to using recycled PET to replace virgin PET, not all demand for PET can be met through recycling [6]. Bottle-grade PET exists as a semi-crystalline thermoplastic with high impact and tensile strength, chemical resistance, and reasonable thermal stability [2], which enables its use in various applications, such as in the development of nanofibers and composites [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many advantages to using recycled PET to replace virgin PET, not all demand for PET can be met through recycling [6]. Bottle-grade PET exists as a semi-crystalline thermoplastic with high impact and tensile strength, chemical resistance, and reasonable thermal stability [2], which enables its use in various applications, such as in the development of nanofibers and composites [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recycled PET fibers have also been produced using centrifugal melt spinning. Zander et al spun recycled PET fibers with a diameter of 4.56 ± 2.97 μm via centrifugal melt spinning at 300 °C [22]. However, the relatively high viscosity of melt-spun material makes it difficult to generate thin fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions and prospects: Hygienic investigations have shown that the product of destruction of the samples of cement-sand compositions, filled with polymers, is a mixture of inorganic amorphous sediment, its main mass consists of CaO, Ca(OH) 2 , Ca(НСО 3 ) 2 97. 4-98.2% of the total mass sediment, Mg(OH) 2 , Al 2 (OH) 3 . Formed products of destruction are non-toxic insoluble or slightly soluble simple inorganic compounds that do not affect adversely the environment and human being.…”
Section: Resultsmentioning
confidence: 99%
“…Выводы и перспективы. Гигиеническими исследованиями установлено, что продуктом деструкции образцов цементно-песчаных композиций, наполненных полимерами, является смесь неорганического аморфного осадка, основную массу которого составляют СаО, Са(ОН) 2 , Са(НСО 3 ) 2 97,4-98,2% от общей массы осадка, а также Мg(ОН) 2 , Al 2 (OH) 3 . Образовавшиеся продукты деструкции являются нетоксичными, нерастворимыми или малорастворимыми простыми неорганическими соединениями, которые не оказывают отрицательного влияния на окружающую среду и человека.…”
unclassified
See 1 more Smart Citation